Estudo comparativo entre estrutura metálica treliçada e de concreto armado em uma edificação - Martins, Iray Fialho (2019)
The metallic structures buildings have several advantages over the reinforced concrete ones. One of its main advantages is the speed, since this method propitiates agility in the stages of its execution. The aim of this study is to design, using a lattice metal structure, an existing building, built on reinforced concrete.The project used is a building of two floors with about 1091 m² per floor. The calculations were made using software and manual calculation. After the design, were collected the material quantitative and its prices through CAIXA's SINAPI table and one of the region's steel structure suppliers. At the end of this comparison, it was observed that the building designed in steel structure is 19% cheaper than the conventional concrete.